Do Female Experts Face an Authority Gap? Evidence from Economics - Hans Henrik Sievertsen; Sarah Smith (Institute of Labor Economics (IZA), 2024)
This paper reports results from a survey experiment comparing the effect of (the same) opinions expressed by male versus female experts. Members of the public were asked for their opinions on topical issues and shown the opinion of either a male or a female economist, all professors at leading US universities. We find, first, that experts can persuade members of the public - the opinions of individual expert economists have an effect on public opinion - and, second, that the opinions expressed by female economists are more persuasive than the same opinions expressed by male economists.
Keywords: A11; D83; J16; 330; economic expertise; persuasion; gender; stereotypes; survey experiments